SISTEM SURAT-MENYURAT BERBASIS WEB DI KANTOR DESA BALE MUSARA - Zainal Zainal; Amna Amna; Hendri Syahputra (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Mailing is one of the Web systems that is now widely used in modern administrative systems. The correspondence system is a system related to administration that virtually concentrates the components of an organization, where data, information, and communication are made through telecommunication media with the aim of building a system that is able to accommodate each element. This correspondence system is built using the SDLC (Software Development Life Cycle) method with the Waterfall Model software development technique. For the use of the correspondence system, a study was conducted entitled